EXPERIENCE OF TREATMENT WITH FENSPIRIDE IN CHILDREN WITH CHRONIC EXUDATIVE OTITIS MEDIA AFTER TYMPANOSTOMY - L.A. Toropova; T.V. Zhuikova; N.I. Marysheva; A.I. Nikolaeva; Yu.S. Maiorova ("Paediatrician" Publishers LLC, 2009)
The trial presents the analysis of factors predisposing to exudative otitis media development in 709 children, needing regular audiologist's check-up. It was shown that dominating risk factor of auditory tube's function disorders is hypertrophy of palatine tonsil (it was detected in 69% of children). Besides, doctors from children's out-patient clinics often use conservative treatment in children with chronic exudative otitis media. Analysis of data obtained at the time of treatment of 180 hospitalized children under the age 1-17 years old with exudative otitis media showed that combination of tympanostomy with fenspiride (Erespal) allows achieving of more significant decrease (1.3 times low) audibility threshold of different oscillations than in children from control (treated without fenspiride).Key words: children, exudative otitis media, timpanostomy, fenspiride.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(4):102-105)